2012
DOI: 10.1007/s00221-012-3049-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning of auditory spectral modulation detection

Abstract: Normal sensory perception requires the ability to detect and identify patterns of activity distributed across the receptor surface. In the visual system, the ability to perceive these patterns across the retina improves with training. This learning differs in magnitude for different trained stimuli and does not generalize to untrained spatial frequencies or retinal locations. Here we asked whether training to detect patterns of activity across the cochlea yields learning with similar characteristics. Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…On the other hand, a recent study on learning monaural spectral modulation detection showed that the magnitude of training-induced improvements decreased with increasing spectral modulation frequency (from 0.5 to 2 ripples/octave, Sabin et al, 2012), potentially complicating the comparison between our two groups. However, if the spectral modulation frequency had indeed played a large role, the training effect would be expected to be more restricted for the warped group then for the control group, opposite to what we have observed.…”
Section: B General Effectiveness Of the Training Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, a recent study on learning monaural spectral modulation detection showed that the magnitude of training-induced improvements decreased with increasing spectral modulation frequency (from 0.5 to 2 ripples/octave, Sabin et al, 2012), potentially complicating the comparison between our two groups. However, if the spectral modulation frequency had indeed played a large role, the training effect would be expected to be more restricted for the warped group then for the control group, opposite to what we have observed.…”
Section: B General Effectiveness Of the Training Methodsmentioning
confidence: 94%
“…This process, called perceptual training (Wright and Fitzgerald, 2001), seems to underlie the process of supervised learning in which neural networks calibrate each other in a goal-directed way (Knudsen, 1994). Since the auditory system is tonotopically organized even up to the auditory cortex (Kaas and Hackett, 2000), perceptual training can be restricted to specific frequencies as shown for frequency discrimination (Recanzone et al, 1993), sensitivity to binaural cues (Wright and Fitzgerald, 2001) and spectral modulation detection (Sabin et al, 2012). Even though the exact neural mechanisms are still the subject of investigation, our training with band-limited DTFs might be considered as frequency-specific supervised training: Over the course of the training, listeners associated the spectral cues below 8.5 kHz with the visually provided spatial information, while the frequencies above 8.5 kHz were not stimulated at all.…”
Section: E Perceptual Trainingmentioning
confidence: 99%
“…Non-acoustical factors, such as perceptual processes, have been proposed to explain the large individual differences reported in studies about discrimination between front and rear sources (Wightman and Kistler, 1999 ) and about sound localization in noise (Andéol et al, 2011 , 2013 ). The perceptual processes involved in the analysis of spectral cues (Drennan and Watson, 2001 ; Sabin et al, 2012 ) and sound localization accuracy with individual HRTFs (Majdak et al, 2010 ) were both found to improve with training in the auditory task. In the latter study, acoustical cues were kept constant but sensory (visual) feedback was provided during training.…”
Section: Introductionmentioning
confidence: 99%
“…All stimuli were 168 ms in duration, including 20-ms raised-cosine ramps. While some studies of spectral modulation perception have used longer-duration stimuli, on the order of 400 ms [ 14 , 19 ], there is precedent in the literature for using stimulus durations as short as 30–100 ms [ 20 , 21 ]. Briefer stimuli may be preferable if they provide the listener with less robust temporal cues to spectral shape.…”
Section: General Methodsmentioning
confidence: 99%
“…As illustrated in Fig 3 , performance in both tasks improved with increasing modulation rate up to 1–2 rpo. This result has been attributed to difficulties comparing spectral features that are distributed widely in frequency [ 21 ]. Above 2–4 rpo, thresholds worsened with increasing modulation rate, a finding attributed to detrimental effects of limited frequency resolution [ 19 ].…”
Section: Experiments 2: Thresholds In Db For Modulation Detection Vs mentioning
confidence: 99%